The concurrent effect of acyclovir and rosemary on glioblastoma cell culture - í–zdemir, Meryem Damla; Göktürk, Dilek (Cellular and Molecular Biology, 2019)
Human cytomegalovirus (HCMV) is a beta herpesvirus which large amount of people in world has interacted with. Recent studies indicated that CMV DNA is associated with several cancer types including "Glioblastoma (GBM)” which is the most common and aggressive type of primary brain cancer. In clinical studies it was shown that several antiviral medicines prolonged life span of glioblastoma patients. One of them is Acyclovir (ACV) which is a type of nucleoside analog, used to cure viral infections and might be a potential treatment supplement for Glioblastoma. In this study we aimed to investigate if ACV had cytotoxic effect on glioblastoma cell line U87 MG and also the effect of ACV on healthy cells. Furthermore it was aimed to search the effect of Rosmarinus Officinalis also known as rosemary which is an aromatic, perennial plant concurrent with ACV on glioblastoma and healthy cells.